2020
DOI: 10.21203/rs.3.rs-72171/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lived Experiences of Iranian ICU Nurses In The Care of Patients With Covid-19: A Phenomenological Study

Abstract: Background: Covid-19 pandemic with its sudden and widespread global outbreak has stunned health care systems. Nurses are at the forefront of fight against this pandemic, and Intensive care unit (ICU) nurses are more at risk of infection as they have a greater interaction with infected patients. Therefore, the present study was conducted to explore the lived experiences of Iranian ICU nurses in the care of patients with covid-19.Methods: This is an interpretive phenomenological study in which, 15 ICU nurses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 17 publications
3
4
0
Order By: Relevance
“…Social isolation, the second theme in the study consisted of the sub-themes of restriction, loneliness and longing, and stigma. An in-depth investigation of the literature indicates similar results to our findings: nurses have negative emotions and go through social isolation and stigmatization; they thus stay away from others, live alone, and feel worthless (Kaçkın et al, 2021; Muz and Yüce Erdoğan, 2021; Shahmari et al, 2020). These emotions experienced by nurses may threaten patient safety by causing a deterioration in the quality of care.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Social isolation, the second theme in the study consisted of the sub-themes of restriction, loneliness and longing, and stigma. An in-depth investigation of the literature indicates similar results to our findings: nurses have negative emotions and go through social isolation and stigmatization; they thus stay away from others, live alone, and feel worthless (Kaçkın et al, 2021; Muz and Yüce Erdoğan, 2021; Shahmari et al, 2020). These emotions experienced by nurses may threaten patient safety by causing a deterioration in the quality of care.…”
Section: Discussionsupporting
confidence: 89%
“…Professionalism, the fifth theme determined in this study, was addressed in the sub-theme of commitment to the profession. An in-depth investigation of the literature indicates similar results to our findings: nurses are proud to be nurses, and they do not give up fighting even in the presence of chronic diseases and however difficult the circumstances (LoGiudice and Bartos, 2021; Shahmari et al, 2020); they love their profession, they continue to fulfill their professional responsibilities to provide the best care for their patients (Karimi et al, 2020; Muz and Yüce Erdoğan, 2021; Shahmari et al, 2020; Şimşek & Günay, 2021); and they try to maintain their role as carers even when that means risking their physical distance (Okuyan et al, 2020). The WHO stated that nurses and other healthcare professionals had also demonstrated their compassion and courage in the face of the epidemic (WHO, 2020).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Being sincere, fulfilling responsibilities, and not giving up are the keys to carrying out tasks; besides, participants always pray to God to start work and ask for care. According to Shahmari et al (2020), nurses showed the spirit of self-sacrifice and did not give up on providing the best care.…”
Section: Survive Physically and Mentally Healthymentioning
confidence: 99%
“…Nurses demonstrated a spirit of self-sacrifice and persisted in giving patients the finest care possible (Shahmari et al, 2020). Nurses' ability to provide care and professional commitment are related to nurses' spiritual health (Chiang et al, 2016).…”
Section: Survive Physically and Mentally Healthymentioning
confidence: 99%